2016
DOI: 10.1038/npp.2016.171
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Deletion of the Nociceptin/Orphanin FQ Receptor in the Rat Confers Resilience to the Development of Drug Addiction

Abstract: The nociceptin (NOP) receptor is a G-protein-coupled receptor whose natural ligand is the NOP/orphanin FQ (N/OFQ) peptide. Evidence from pharmacological studies suggests that the N/OFQ system is implicated in the regulation of several addiction-related phenomena, such as drug intake, withdrawal, and relapse. Here, to further explore the role of NOP system in addiction, we used NOP (− / − ) rats to study the motivation for cocaine, heroin, and alcohol self-administration in the absence of N/OFQ function. Condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
46
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 55 publications
1
46
2
Order By: Relevance
“…The above findings demonstrate that NOP receptor activation attenuates alcohol drinking and seeking in rats. However, these findings appear to be inconsistent with molecular data that show that (a) animals with heightened N/OFQ‐NOP expression, either innate (msP rats), or adaptive (post‐dependent Wistar rats) drink higher amounts of alcohol and are more prone to relapse (Aujla et al, ; Cippitelli et al, ; Economidou et al, ; Hansson et al, ) and (b) engineered rats with constitutive NOP receptor deletion self‐administer less alcohol compared with wild type controls (Kallupi et al, ). More importantly, a recent study demonstrated that the selective NOP receptor antagonist LY2940094 attenuated alcohol intake and relapse to alcohol seeking in both msP and Indiana alcohol‐preferring (P) rats (Rorick‐Kehn et al, ).…”
Section: Introductionmentioning
confidence: 93%
“…The above findings demonstrate that NOP receptor activation attenuates alcohol drinking and seeking in rats. However, these findings appear to be inconsistent with molecular data that show that (a) animals with heightened N/OFQ‐NOP expression, either innate (msP rats), or adaptive (post‐dependent Wistar rats) drink higher amounts of alcohol and are more prone to relapse (Aujla et al, ; Cippitelli et al, ; Economidou et al, ; Hansson et al, ) and (b) engineered rats with constitutive NOP receptor deletion self‐administer less alcohol compared with wild type controls (Kallupi et al, ). More importantly, a recent study demonstrated that the selective NOP receptor antagonist LY2940094 attenuated alcohol intake and relapse to alcohol seeking in both msP and Indiana alcohol‐preferring (P) rats (Rorick‐Kehn et al, ).…”
Section: Introductionmentioning
confidence: 93%
“…Genetic deletion of the nociception receptor in rats resulted in lower alcohol consumption compared to wildtype controls, while saccharin intake was unaltered (Kallupi et al, 2017). Further, systemic administration of NOP antagonists reduced alcohol self-administration in wildtype rats but was without effect in NOP-deficient rats (Kallupi et al, 2017).…”
Section: Mechanisms Underlying Chronic Alcohol Stress and Drinkimentioning
confidence: 99%
“…Genetic deletion of the nociception receptor in rats resulted in lower alcohol consumption compared to wildtype controls, while saccharin intake was unaltered (Kallupi et al, 2017). Further, systemic administration of NOP antagonists reduced alcohol self-administration in wildtype rats but was without effect in NOP-deficient rats (Kallupi et al, 2017). These results align with another report showing that oral administration of a NOP antagonist reduced alcohol consumption, motivation to work for alcohol, and stress (yohimbine)-induced reinstatement of alcohol-seeking behavior in rats (Rorick-Kehn et al, 2016).…”
Section: Mechanisms Underlying Chronic Alcohol Stress and Drinkimentioning
confidence: 99%
“…NOR activation has also been shown to exert anxiolytic effects in different models of stress (Jenck et al, ; Köster et al, ) and NOR knockout mice exhibit increased learning ability, memory, and hippocampal long term potentiation (Mamiya, Noda, Nishi, Takeshima, & Nabeshima, ; Noda et al, ; Yu and Xie, ). Furthermore, NOR‐deficient mice also develop altered responses to morphine (Chung, Pohl, Zeng, Civelli, & Reinscheid, ; Rizzi et al, ; Mamiya et al, ; Ueda, Inoue, Takeshima, & Iwasawa, ; Ueda et al, ), nicotine (Sakoori and Murphy, ), heroin (Kallupi et al, ), ethanol (Kallupi et al, ), and cocaine (Kallupi et al, ; Marquez, Hamid, & Lutfy, ; Marquez, Nguyen, Hamid, & Lutfy, ), indicating a possible role of the nociceptin system in drug addiction.…”
Section: Introductionmentioning
confidence: 99%
“…morphine (Chung, Pohl, Zeng, Civelli, & Reinscheid, 2006;Rizzi et al, 2000;Mamiya et al, 2001;Ueda, Inoue, Takeshima, & Iwasawa, 2000;Ueda et al, 1997), nicotine (Sakoori and Murphy, 2009), heroin (Kallupi et al, 2017), ethanol (Kallupi et al, 2013), and cocaine (Kallupi et al, 2017;Marquez, Hamid, & Lutfy, 2013;Marquez, Nguyen, Hamid, & Lutfy, 2008), indicating a possible role of the nociceptin system in drug addiction.…”
mentioning
confidence: 99%